Pathogenicity of Chrysoporthe cubensis to Eucalyptus grandis and E. urophylla clones in the Southeastern of Mexico - Juárez-Palacios, J. Carlos; Honorato-Salazar, J. Amador; Vázquez-Silva, Luis; Parraguirre-Lezama, J.F. Conrado (Instituto de Ecología, A.C., 2013)
Eucalyptus grandis S.T. Blake and E. urophylla Hill ex Maiden are the most promissory speciesfor forest plantations in the southeastern of Mexico. Their production potential is threaten by the cankerpathogen, Chrysoporthe cubensis (Bruner) Gryzenhout & M.J. Wingf., which affects most of the treesand can cause damage of about 43,6% in E. grandis trees and up to 40% of the merchantable volumeof both species. This study was carried out to assess the pathogenicity of C. cubensis in six E. grandisand four E. urophylla clones. Four isolates of C. cubensis were inoculated on young twigs of botheucalyptus clones in laboratory conditions and the highly pathogenic isolate was selected after thirtydays. Four plants of each clone were subsequently inoculated in greenhouse conditions with the isolateA3, which was the most virulent, to determine their tolerance to the pathogen after thirteen months. Inboth trials, lesion length in the bark was measured. Results showed that the four isolates of C. cubensis eucaliptoare capable of causing lesions on young twigs of Eucalyptus clones and significant differences were observed between clones and isolates. All tested clones were susceptible to isolate A3, but exhibited varying levels of tolerance to the attack.